MRI compatibility of orthodontic brackets and wires: systematic review article - Adrienn Dobai; Fanni Dembrovszky; Tamás Vízkelety; Péter Barsi; Fanni Juhász; Csaba Dobó-Nagy (BMC, 2022)
Abstract Background Before the magnetic resonance imaging (MRI) examination fixed orthodontic devices, such as brackets and wires, cause challenges not only for the orthodontist but also for the radiologist. Essentially, the MRI-safe scan of the fixed orthodontic tools requires a proper guideline in clinical practice. Therefore, this systematic review aimed to examine all aspects of MRI-safe scan, including artifact, thermal, and debonding effects, to identify any existing gaps in knowledge in this regard and develop an evidence-based protocol. Methods The Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) statement was used in this study. The clinical question in "PIO" format was: "Does MRI examination influence the temperature of the orthodontic devices, the size of artifacts, and the debonding force in patients who have fixed orthodontic bracket and/or wire?" The search process was carried out in PubMed, PubMed Central, Scopus, and Google Scholar databases. The search resulted in 1310 articles. After selection according to the eligibility criteria, 18 studies were analyzed by two reviewers. The risk of bias was determined using the Quality In Prognosis Studies tool. Results Out of the eligible 18 studies, 10 articles examined the heating effect, 6 were about the debonding effect, and 11 measured the size of artifact regarding brackets and wires. Considering the quality assessment, the overall levels of evidence were high and medium. The published studies showed that heating and debonding effects during MRI exposure were not hazardous for patients. As some wires revealed higher temperature changes, it is suggested to remove the wire or insert a spacer between the appliances and the oral mucosa. Based on the material, ceramic and plastic brackets caused no relevant artifact and were MRI-safe. Stainless steel brackets and wires resulted in susceptibility artifacts in the orofacial region and could cause distortion in the frontal lobe, orbits, and pituitary gland. The retainer wires showed no relevant artifact. Conclusions In conclusion, the thermal and debonding effects of the fixed orthodontic brackets and wires were irrelevant or resoluble; however, the size of the artifacts was clinically relevant and determined most significantly the feasibility of fixed brackets and wires in MRI examination.